Mental health disorder in chronic liver disease: a questionnaire survey - Long, Jiang; Pei, Xiong; Jiang, Wei; Wang, Xiaoling; Wu, Dongbo; Tang, Xiangdong; Zhou, Taoyou (Frontiers in Psychiatry, 2024)
The mental health of patients with chronic liver disease (CLD) warrants greater attention and understanding, especially concerning its risk factors.Method: Patients from our hospital's hepatology clinic were consecutively enrolled and completed a questionnaire assessing anxiety, depression, and sleep quality using the GAD-7, PHQ-9, and PSQI scales, respectively. Reliability and validity were evaluated with Cronbach's α and Kaiser-Meyer-Olkin (KMO). Continuous and categorical variables were analyzed using the Mann-Whitney U and Chi-square tests. Univariate and multivariate logistic regression were used to identify risk factors, while restricted cubic spline (RCS) were used to explored non-linear associations. Subgroup analyses were stratified by sex, age, and education.Result: A total of 1030 questionnaires were collected, and after quality control, 1003 were included. 56.2% (564/1003), 53.2% (534/1003), and 67.4% (676/1003) individuals had anxiety, depression, and sleep disorders. Differences in age, gender, and education level were observed (P<0.05).Subgroup analysis showed similar demographic trends. Univariate and multivariate regression analysis found age negatively correlated with anxiety (OR=0.98, 95%CI=0.97-0.99, P=0.02) and depression (OR=0.98, 95%CI=0.96-0.99, P<0.001), but positively correlated with sleep disorders (OR=1.03, 95%CI= 1.01-1.05, P< 0.001); males are less prone to anxiety (OR=0.68, 95%CI=0.52-0.88, P=0.004) and sleep disorders (OR=0.72, 95%CI: 0.55-0.94, P=0.02); university degree is more susceptible to depression (OR=1.36, 95%CI=1.04-1.77, P=0.02) and anxiety (OR=1.45, 95%CI=1.11-1.89, P=0.007). RCS analysis suggested a linear relationship between the age and affective disorders among different population.Young individuals, female, and those with higher education are more vulnerable to mental health, warranting increased attention.